Variability of fruit shelf-life of commercial tomatoes and their hybrids crossing with insensitivity ethylene mutant tomato Sletr1-2 - Wiguna, Gungun; Bachtiar, Nedya Putri; Anas, Anas; Wicaksana, Noladhi; Mubarok, Syariful; Saadah, Imas Rita (Jurnal Ilmu Pertanian, 2024)
Tomatoes are climacteric fruits that experience a surge in respiration rate and ethylene production. This condition affects the fruits’ physiological deterioration, shortens their shelf-life, and degrades the quality of tomatoes. The study aimed to enhance the shelf-life of commercial tomatoes with different genetic backgrounds by utilizing the Sletr1-2 mutant, which has a lower sensitivity to ethylene. A randomized block design (RBD) was applied to achieve this goal, where 12 different plant genotypes were considered as treatments, and each treatment was replicated four times.  The results showed that fruit shelf-life was extended by crossing commercial tomatoes with Sletr1-2 mutant tomatoes. Genetic variability for all shelf-life characteristics were narrow. In contrast, there were broad phenotypic variability for fruit hardness and weight loss characteristics.